2011
DOI: 10.1007/s00531-011-0720-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporal correlation of magmatic-tectonic events in the lower and upper crust in north-east Australia

Abstract: Hf model ages yielded by rutiles in a garnetrich lower-crustal granulite xenolith from the McBride Province and whole-rock Nd and Hf model ages for the plagioclase-and garnet-rich Chudleigh and McBride granulites overlap with the well-defined U-Pb ages for detrital zircons and zircons in granitoids (Murgulov et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…It has been revealed that the easternmost block is very thin, of about ~50-60 kilometers with no thermal indication of a plume beneath eastern Australia. Instead, rifting was controlled by slabrollback and back-arc extension started in the Mesozoic and continued to the Cenozoic as presumed by numerous previous studies (e.g., Allan et al 1997;Schellart et al 2006;Kositcin et al 2009;Murgulov et al, 2012). Such thinned lithosphere is consistent with our model, that supports continental extension and possibly following thermal relaxation.…”
Section: Mantle Fluids In the Lithospheric Mantle In Extensional Settingsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been revealed that the easternmost block is very thin, of about ~50-60 kilometers with no thermal indication of a plume beneath eastern Australia. Instead, rifting was controlled by slabrollback and back-arc extension started in the Mesozoic and continued to the Cenozoic as presumed by numerous previous studies (e.g., Allan et al 1997;Schellart et al 2006;Kositcin et al 2009;Murgulov et al, 2012). Such thinned lithosphere is consistent with our model, that supports continental extension and possibly following thermal relaxation.…”
Section: Mantle Fluids In the Lithospheric Mantle In Extensional Settingsupporting
confidence: 90%
“…During the Cenozoic, continued extension resulted in the formation of widespread intraplate basalt fields (Murgulov et al, 2012), transporting numerous mantle-derived xenoliths to the surface along the eastern margin of Australia (O'Reilly, 1988). The ages of the ATVP volcanic forms vary between 10 ka and 3 ka, and the pyroclastic cone of Mt.…”
Section: A C C E P T E D Mmentioning
confidence: 99%